Factors Influencing Saudi Arabia's Foreign Policy Towards China During the Reign of King Salman - Ali akbar Asadi (رهیافتهای سیاسی و بین المللی)
Introduction: In recent years, there has been a notable trend in Iran's environment, characterized by China's increasing presence and influence in the Middle East, as well as its endeavors to strengthen relations with the Persian Gulf countries. Given America's longstanding presence in the Persian Gulf and its strategic partnerships with Arab countries, China's involvement has significantly contributed to the complexity of regional issues. For instance, Saudi Arabia, the largest Arab country in the Persian Gulf, has expanded its interactions with China focusing on energy, and in practice, China has become Riyadh's first commercial and economic partner.The main aim of this article is to provide a comprehensive analysis of the essential factors and significant changes that have shaped Saudi Arabia's foreign policy towards China during the reign of King Salman. It addresses the following questions: what are the determining elements of Saudi Arabia's foreign policy regarding China in the years after 2015, and how have these factors led to the prioritization of extensive cooperation and a comprehensive strategic partnership between the two countries?Methods and Conceptual Framework: To identify and explain the underlying factors behind Saudi Arabia's shift in foreign policy toward China, this study adopts the conceptual framework of Neoclassical Realism and uses an explanatory methodology. Structural realists emphasize the importance of changes in the international system and the balance of global power in shaping countries' foreign policies. However, neoclassical realists emphasize the significance of internal factors in understanding a government's foreign policy. Therefore, a substantial part of this research focuses on investigating the impact of domestic variables on the strategic choices made by the Saudi government towards China.Results and Discussion:The findings of this research indicate that the rise of China and its consequences at international and regional levels are the main and independent variables shaping Saudi Arabia's new foreign policy towards China. However, while international factors have a substantial impact, there are also specific domestic factors that serve as intermediate variables in Saudi Arabia's strategies toward China. At this level, several crucial factors contributed to the development of Saudi cooperation with China during King Salman's era. These factors included the capacities of national power, the rise of authoritarianism, unity and consensus among Saudi elites, the emergence of new Saudi nationalism, the centralization of authoritarian development, and evolving perceptions of Saudi leaders regarding recent international and regional transformations.Saudi Arabia and China's relations have shown a positive and steadily growing trend over the past three decades. However, it is during the reign of King Salman that these relations have entered a new stage, known as a comprehensive strategic partnership. This partnership is characterized by increased cooperation in the commercial, economic, and political spheres. The emergence of a new generation of Saudi leaders, led by Muhammad bin Salman, has significantly influenced the transformation of Saudi policies. These leaders possess a deep and comprehensive understanding of international trends and conditions, which has played a pivotal role in reshaping Saudi Arabia's approach. Particularly noteworthy is their realistic understanding of the shift of power from West to East, their pragmatic approach in relations with regional and global actors, and the new definition of national interests.Conclusion: In the new circumstances, despite the persistence of some uncertainties regarding the overall direction of Saudi Arabia's foreign policy, the continuation of the country's military-security cooperation with the United States remains evident. However, the prioritization of authoritarian development by Saudi leaders is a significant driver that will lead to the continuation and development of Saudi Arabia-China relations in the coming years.